Les relatives en américain contemporain - Françoise Dubois-Charlier (Anglophonia)
This paper presents an analysis of relatives clauses in a corpus of American English (a contemporary novel).Our first aim was to study whether the syntax of relatives clauses is the same in American English and in British English - and the study shows that the two systems differ in several important ways.Our second aim was to revive a methodology: the idea was to approach the data with an open mind, to gather and analyse all the occurrences in a complete discourse, to ‘listen’ to what the data have to say - as opposed to an approach frequently used in recent studies, where the argumentation is theory-based and theory-oriented, and examples collected here and there are mere illustrations of what is posited.